Innovative impact assessment of electric vehicles charging loads on distribution transformers using real data - Godina, R.; Rodrigues, E. M. G.; Paterakis, N. G.; Erdinc, O.; Catalao, J. P. S. (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
Widespread adoption of Electric Vehicles (EVs) could bring social and economic benefits. The effort of promoting the use of EVs in transportation is indispensable to meet the climate change related targets and to reduce the dependency on the ever unstable prices of diminishing fossil fuels. However, there are still many uncertainties in the market regarding the acceptability of EVs by the final consumers. As a new contribution with respect to earlier studies, this paper assesses the impact of EV charging load on the dielectric oil deterioration of two real Power Distribution Transformers (PDTs), one residential and one industrial, located in the insular grid of Sao Miguel. A PDT thermal model is used to estimate the hot-spot temperature given the load ratio. Real data are used for the main inputs of the model, namely, the daily residential load curve, the daily private industrial client load curve, the PDT parameters, time-of-use rates and EV parameters. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Battery; Distribution transformer; EV charging; Loss-of-life; Transformer ageing; POWER-SYSTEMS; DEMAND; ENERGY; PENETRATION; Thermodynamics; Energy & Fuels; Mechanics